Exploring Educators’ Views on the Impact of Covid-19 Pandemic in the Development of Children under the Age of 3 - Sotiropoulou, Eleni; Venetas, Georgios Stroungis; Bercovits, Anastasia; Giannakou, Vasiliki (Global Journal of Educational Studies, 2024)
The covid-19 pandemic affected the lives of all people worldwide. The unprecedented situations faced by people of all ages affected their mental and physical health. In this context, children are an especially vulnerable group as their development is in full swing and they have not yet acquired the skills to cope with stressful situations. Therefore, the purpose of this study is to explore the views of 31 educators working in Attica (Greece) regarding the changes they observe in the development of children under the age of 3. In addition, the research addresses the type of activities that cannot be carried out in nurseries due to covid -19 health protocols, the alternative methods used by the educators and their suggestions for future interventions. The research instrument used was the semi-structured interview and the data was analyzed using thematic analysis. The results of the study show that the educators observe changes in the social, emotional and language domains of children's development. Specifically, children seem to suffer from strong attachment, anxiety, hyperactivity, inability to regulate emotions, fear of social interactions, and slow vocabulary development-especially foreign students. The researchers anticipate that the results of the present study will contribute to the investigation of the developmental implications of the covid-19 pandemic in children under 3 years old and provide useful information to educators for future interventions in nurseries.